Anaemia in pregnant women. Principles of therapy today - N. A. Korotkova (Медицинский совет, 2015)
The article tells about the epidemiology of iron deficiency with the focus on iron metabolism, the etiology and pathogenesis of iron deficiency in pregnant and postpartum women, approaches to the diagnosis of iron deficiency anemia and iron deficiency, methods of prevention and treatment of iron deficiency conditions.